Pengaruh Model Pembelajaran Kooperatif Tipe Stad dan Pemberian Soal Open-Ended Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau Dari Kemampuan Awal Matematika - Rumapea, Rindu (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
This study aims to determine the effect of giving Open-Ended questions in cooperative learning model, STAD type, to students’ mathematical problem solving ability. This study was conducted in SMP Santa Theresia Central Jakarta. The method used in this study is quasi-experimental. The technics of data collection of this study are test of mathematical problem solving abilty and Mathematics initial knowledge. The results of this study show that (1) mathematical problem solving abilty of students who are taught by giving Open-Ended questions in cooperative learning model, STAD type, is higher than the abilty of mathematical problem solving of those who are taught by using conventional learning model, (2) there is no interaction between learning model and Mathematics initial knowledge to mathematical problem solving abilty, (3) there is significant difference of mathematical problem solving ability of students who are taught by giving Open-Ended questions in cooperative learning model, STAD type and mathematical problem solving ability of students who are taught by using conventional learning model among student group whose Mathematics intial knowledge is high, (4) there is no significant difference of mathematical problem solving ability of students who are taught by giving Open-Ended questions in cooperative learning model, STAD type and mathematical problem solving ability of students who are taught by using conventional learning model among student group whose Mathematics intial knowledge is low.